Caffeine prevents exercise-induced hypoglycemia in trained runners - Reis Weber, V. M.; Queiroga, M. R.; Kiihn, A. L.; Maneck Malfatti, C. R.Jessica Wouk, Sandra Aires Ferreira, Luiz Augusto da Silva (Journal of Human Sport & Exercise, 2019)
The objective of this study was to analyze the physiological, biochemical, and perceptive effects of caffeine intake in marathon runners after a maximal treadmill stress test. The sample comprised randomly selected 12 male athletes of long distance races (42,125 km). The participants performed the maximal stress test twice, after ingesting a placebo and caffeine (dose de 6 mg.kg-1) capsules, using double-blind methodology. Anthropometric parameters, heart rate (HR), blood pressure (BP), and subjective perception of effort (SPE) were evaluated before, during, and after the test. Blood samples for analyses of glucose, lactate (LAC), and triglyceride (TG) levels were also collected at the same time. The maximal stress test was performed on a treadmill, and parameters such as VO2 max and subjective perception of effort (SPE) were analyzed. Before the trial and caffeine/placebo ingestion, capillary blood was collected by finger puncture for subsequent analyses. Subsequently, the maximal treadmill stress test was initiated with a 3-minute low intensity warm-up phase. The trial continued with the maximal treadmill stress test protocol, followed by a cool-down period (walk) until HR normalization. The athletes remained seated for 10 minutes, and during this period, HR and BP were measured, and blood samples were collected. HR values presented no difference between groups. However, glucose, TG, and LAC levels different after caffeine intake. The results of the present study demonstrated that caffeine ingestion modifies glucose, TG, and LAC availability during exercise in trained runners.